2011
DOI: 10.5194/acp-11-667-2011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental simulation of satellite observations of 100 kHz radio waves from relativistic electron beams above thunderclouds

Abstract: Abstract. Relativistic electron beams above thunderclouds emit 100 kHz radio waves which illuminate the Earth's atmosphere and near-Earth space. This contribution aims to clarify the physical processes which are relevant for the spatial spreading of the radio wave energy below and above the ionosphere and thereby enables an experimental simulation of satellite observations of 100 kHz radio waves from relativistic electron beams above thunderclouds. The simulation uses the DEMETER satellite which observes 100 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, these processes remained sub-visual in the optical observations reported in this work, and it is not clear why such a hypothetical process would emit low frequency electromagnetic radiation while the sprite itself does not. It is interesting to note that the low frequency electromagnetic radiation reported here can be observed in space as a result of its transionospheric propagation (Füllekrug et al, 2011(Füllekrug et al, , 2009) and it may be associated with high frequency electromagnetic radiation (Parrot et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…However, these processes remained sub-visual in the optical observations reported in this work, and it is not clear why such a hypothetical process would emit low frequency electromagnetic radiation while the sprite itself does not. It is interesting to note that the low frequency electromagnetic radiation reported here can be observed in space as a result of its transionospheric propagation (Füllekrug et al, 2011(Füllekrug et al, , 2009) and it may be associated with high frequency electromagnetic radiation (Parrot et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…It is interesting to note that a recent detailed comparison of ground based optical sprite observations in southern France with electric field recordings on board the DEMETER satellite on 17 November 2006 (Parrot et al 2013), revealed low frequency radio signals up to ∼130 kHz associated with the sprite and/or the causative lightning discharge which have never been observed before in association with ordinary lightning discharges ( figure 4). Given that the ionosphere attenuates ∼100 kHz radio signals by ∼2 orders of magnitude (Füllekrug et al 2011a), the signal intensity of the lightning and/or sprite was undoubtedly exceptionally large. This observation shows that powerful low frequency radio signals associated with sprite producing lightning, as reported here, can be observed in space with unprecedented temporal and spectral resolution which is the aim of the French TARANIS satellite due to be launched in 2015 (Blanc et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The locations of these electromagnetic noise sources are closely monitored and mapped around the world by the use of sensitive electromagnetic recordings on board of satellites. For example, the electromagnetic radiation from transmitters for submarine communication [ Sauvaud et al , ] and marine navigation [ Füllekrug et al , , ] escapes from the Earth ionosphere waveguide into near‐Earth space in the Whistler mode [e.g., Lefeuvre et al , ; Helliwell , ]. These low‐frequency radio communication transmitters are widely used for geophysical exploration, for example, to study particle precipitation from the radiation belts into the Earth's atmosphere and the impact of lightning discharges on the upper atmosphere [e.g., Denton et al , ; Haldoupis et al , , ; Sauvaud et al , ; Inan et al , ; Horne et al , , and references therein].…”
Section: Introductionmentioning
confidence: 99%